The Act on Counteracting Food Waste – an attempt of its evaluation - Sokołowski, Łukasz Mikołaj (Przegląd Prawa Rolnego, 2019)
The article is a voice in the discussion on the legitimacy of the solutions adopted in the Act on Counteracting Food Waste. The author assesses both the direction of the legislator’s actions as well as individual legal instruments provided for in the new regulations. Despite many critical comments and objections to the solutions adopted, adoption of separate legal regulations in this respect should be assessed positively. The measures taken may constitute the first steps on the way to the implementation of comprehensive solutions, being at the same time a manifestation of the legislator’s efforts to ensure food sovereignty, based among other things on a closed-circuit economy.